2013
DOI: 10.1088/0169-5983/46/1/015503
|View full text |Cite
|
Sign up to set email alerts
|

Camassa–Holm equations and vortexons for axisymmetric pipe flows

Abstract: Abstract. In this paper, we study the nonlinear dynamics of an axisymmetric disturbance to the laminar state in non-rotating Poiseuille pipe flows. In particular, we show that the associated Navier-Stokes equations can be reduced to a set of coupled Camassa-Holm type equations. These support inviscid and smooth localized travelling waves, which are numerically computed using the Petviashvili method. In physical space they correspond to localized toroidal vortices that concentrate near the pipe boundaries (wall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…The observed deviations from Taylor’s hypothesis appear to be the signature of the dispersive nature of turbulence. Moreover, the observed wave dispersion fairly agrees with the theoretical dispersion predicted for axisymmetric flows 18 , 19 , 21 .…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The observed deviations from Taylor’s hypothesis appear to be the signature of the dispersive nature of turbulence. Moreover, the observed wave dispersion fairly agrees with the theoretical dispersion predicted for axisymmetric flows 18 , 19 , 21 .…”
Section: Discussionsupporting
confidence: 83%
“…Fedele and Dutykh 18 , 19 investigated the dynamics of non-rotating axisymmetric pipe flows in terms of nonlinear soliton bearing equations. They showed that at high Reynolds numbers, the dynamics of perturbations to the laminar flow obey a coupled system of nonlinear Camassa–Holm (CH) equations 20 .…”
Section: Wave Dispersion In Axisymmetric Navier–stokes Flowsmentioning
confidence: 99%
See 3 more Smart Citations